Implementasi Konsep Sanctuary Pada Perancangan Interior Sanctuary Spa & Relaxation Centre di Bali - Christina Wijayanti; Stephanus P Honggowidjaja (Intra, 2013)
Bali is an island which always be a tourist destination, both local tourists and foreign tourists. It makes the property entrepreneur compete to build the functional and aesthetic architecture interior, start from nature tourism, culinary tourism, up to shopping tourism. Many attractions in Bali make the most of Bali’s population choose livelihoods related to the world of tourism. For the people of Indonesia and overseas, saturated daily routines at their origin place make them yearn to relax and restore the body's vitality. It makes the fitness center and body treatments like spa is many emerging, such as Sanctuary Spa & Relaxation Centre in Surabaya.                In this era, woman spa design development grows rapidly including in Bali. But, in the midst of these developments, there are many spa places encountered by incorporating elements of foreign culture and use imported products. It makes local culture and domestic products are less widely known. Therefore is necessary a new spa design like Sanctuary Spa & Relaxation Centre in Bali so the local culture and domestic products can be applied and be able to compete in the global marketplace.